Characterization of defects in mono‐like silicon for photovoltaic applications using X‐ray Bragg diffraction imaging. (1st June 2015) - Tsoutsouva, M. G.; Oliveira, V. A.; Baruchel, J.; Camel, D.; Marie, B.; Lafford, T. A.
<x xml:space="preserve">Abstract</x> Rocking curve imaging (projection and section X‐ray topography) has been used to study the generation and propagation of defects at the junctions between and above the seed crystals in mono‐like silicon ingots. The images of different kinds of defects such as precipitates, dislocations and twins in the integrated intensity, full width at half‐maximum and peak position maps resulting from the experiment have been studied. The qualitative and quantitative information that can be extracted from these maps, in particular the contrast of the images of the various defects, is discussed. These defects have a detrimental effect on solar cell efficiency and their detailed investigation allows clues to be obtained in order to improve the growth process. This work shows that synchrotron X‐ray diffraction imaging techniques, because of their high angular resolution (<10−4°) and large field of view (several mm2), constitute a powerful tool for investigating the initial stages of growth of directionally solidified mono‐like silicon.